From One Ontology to the Set of All Possible - Khazieva, Natalia O. (Journal of History Culture and Art Research, 2017)
In the framework of hundreds of ontologies that already exist today, it would seem impossible to build other buildings of theories about the world. Any "new" thought will only be an element, a brick in defense and strengthening of a separate theory, or a stumbling block to the new great minds of mankind leading to new reflections and clarifications. Everyone who dared to reconsider the very foundations of the whole being of mankind was a kind of revolutionary and had the opportunity to be remembered as a great scientist, philosopher, artist, writer, thinker. Establishing a completely new and untested before the foundations of being, a person is able to discover unprecedented worlds, the worlds that had not previously imagined by anyone. This is what happened with the discovery of non-Euclidean geometry. The study is about the new ontologies that saw the light after this event, the new conditions for the existence of man, his renewed place in a very complicated world, and the consequences of such drastic changes.